2011
DOI: 10.1017/s1368980011003119
|View full text |Cite
|
Sign up to set email alerts
|

Household food insecurity and hunger among households in Sidama district, southern Ethiopia

Abstract: Objective: To examine household food insecurity and hunger in Sidama Zone, one of the most populous zones in southern Ethiopia. Design: Cross-sectional survey administered individually by trained interviewers. Food insecurity was calculated with both the Household Food Insecurity Access Scale (HFIAS) and the Household Hunger Scale (HHS), developed by the Food and Nutrition Technical Assistance Project. Setting: Rural households from ten kebeles (the smallest administrative district) selected from two agro-clim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
63
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 13 publications
11
63
4
1
Order By: Relevance
“…However, when aggregated according to year, HFIAS scores were much higher during the mid to late 1990s (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) compared to the 2000s (0-2) (data not shown), which coincides with previous reports that the food situation was worse in the 1990s [1,[29][30][31]. The food security level immediately before leaving North Korea was worse than that in Tanzania (48.1% of households severely food insecure) [22] or Ethiopia (47.8% of households severely food insecure) [23] determined by HFIAS.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, when aggregated according to year, HFIAS scores were much higher during the mid to late 1990s (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) compared to the 2000s (0-2) (data not shown), which coincides with previous reports that the food situation was worse in the 1990s [1,[29][30][31]. The food security level immediately before leaving North Korea was worse than that in Tanzania (48.1% of households severely food insecure) [22] or Ethiopia (47.8% of households severely food insecure) [23] determined by HFIAS.…”
Section: Discussionsupporting
confidence: 89%
“…This study examined household food security using the Household Food Insecurity Access Scale (HFIAS) [19]. HFIAS is thought to be a well-developed scale to determine food security at the household level in food insecure environments [19,20] and has been applied in various countries [21][22][23][24]; therefore it was suitable for this study. Since HFIAS was originally developed in English, the questions were translated first to Korean and then back into English; differences between the original and back-translated version were minimized.…”
Section: Food Securitymentioning
confidence: 99%
See 1 more Smart Citation
“…One can ask whether, in a crosssectional survey, it is able to effectively discriminate between food-secure and food-insecure households. Previous studies (3,(12)(13)(14)(15)(16)(17)(18) showed that the HFIAS is correlated with objective food intake-based measures of food security and is thus cross-sectionally valid. In a longitudinal survey that follows the same households over time, the main concern is the inter-temporal validity of the index.…”
mentioning
confidence: 99%
“…The aspect of household food security has received increased attention particularly due to deteriorating economic conditions worldwide (Regassa and Stoecker, 2011). Food security is understood to exist when all people have physical, social and economic access to sufficient, safe and nutritious food (at all times), to meet their dietary smallholder households in three different districts of the Masvingo Province of Zimbabwe.…”
Section: Introductionmentioning
confidence: 99%